FRI0268 Ultrasound vs. magnetic resonance imaging in diagnosis of primary sjÖgren's syndrome. (15th June 2017) - Haidmayer, A; Magyar, M; Stradner, MH; Zordo, T De; Lutfi, A; Unger, B; Graninger, WB; Hermann, J; Dejaco, C
Abstract : Background: Salivary gland (SG) biopsy is the gold standard for the diagnosis of primary Sjögren's syndrome (pSS). Ultrasound (US) and magnetic resonance imaging (MRI) of the SG are emerging techniques. The comparison of both imaging methods for diagnosis and assessment of functional limitation is yet not well investigated. Objectives: To assess the accuracy of US and MRI and to define possible cutoff values for the diagnosis of pSS. Methods: Twenty-three patients with pSS according to AECG criteria and typical histology of the SG biopsy and 12 patients with sicca-syndrome and normal SG histology were included in the study. Two experienced ultrasound experts (C.D. 6y, T.D.Z. 5y) did ultrasound of the SG using a B-mode score (0–48 points [1]) and real-time sonoelastography (RTS; 0–16 pts [2]). Morphology of the parotid glands was also assessed by MRI (0–12 pts). We obtained clinical data (C-reactive protein (CRP), antinucleary-antibodies (ANA), Ro-/La-antibodies, Gamma globulins, patient questionaires ESSDAI and SSDI). The statistically analysis was carried out using Kolmogorov-Smirnov-test, student's t-test, or Man-Whitney-U-test. Correlations were performed using Spearman-rang-correlations. Results: Patients with pSS had significantly higher B-mode- (average =25 [2–44] vs. 9 [1–20], p<0.001) and RTS-scores (6.5 [2–13] vs. 4 [1–9], p<0.001) than sicca-patients. The same was also found for MRI-assessment (6, 96 vs. 2, 33, p=0.001). In a Spearman rank correlation, clinical parameters were linked to the imaging techniques The B-mode showed significant inverse correlations with the Saxon-test (r=-0.505, p=0.002) and a positive correlation with MRI (r=0.792, p<0.0001). No correlation was found for the activity scores ESSDAI (p=0.221) or SSDI (p=0.219). The MRI score had an inverse correlation with the Saxon-test (r=-0.523, p=0.001). Both imaging techniques showed no relationship with ESR or CRP. We also generated ROC curves of both imaging methods to define possible cutoff values for the diagnosis. For B-Mode we would recommend a value of 12 points (sensitivity 82, 6% and specificity 91, 7%) and for MRI 3.5 points (78, 3% and 91, 7%). Conclusions: Sonography and MRI detected typical morphological changes in the SG of pSS with high sensitivity and specificity. Both methods could become valuable tools for the diagnosis of pSS. References: Hocevar, Ambrozic A, Rozman B, Kveder T, Tomsic M. Ultrasonographic changes of major salivary glands in primary Sjogren's syndrome. Diagnostic value of a novel scoring system. Rheumatology (Oxford). 2005;44(6):768–72. Rubaltelli, Corradin S, Dorigo A, Stabilito M, Tregnaghi A, Borsato S, Stramare R. Differential diagnosis of benign and malignant thyroid nodules at elastosonography. Ultraschall Med. 2009;30(2):175–9. Disclosure of Interest: None declared